Ethnopharmacological exploration and isolation of HIV-1 latency-reversing agents from Sudanese medicinal plants - Elamin, Khaled M.; Kishimoto, Naoki; Kawahara, Teppei; Idris Elbashir, Sara Mustafa; Yasutake, Tae; Wada, Mikiyo; Hitora, Yuki; Kordofani, Maha; Osman, Wadah; Elbashir, Mustafa Idris; Misumi, Shogo (Frontiers in Pharmacology, 2025)
HIV-1 infection remains a major health challenge, especially in resource-limited settings such as Sudan, where traditional medicine is widely practiced for managing infectious diseases, including HIV/AIDS. In this study, we selected ten Sudanese medicinal plants traditionally used to treat immune-related and infectious diseases. The selection was based on ethnobotanical reports and local knowledge of HIV/AIDS-related treatments. Crude extracts were prepared using either absolute methanol or 50% ethanol via maceration, resulting in a total of 20 extracts. The extracts were then screened for HIV-1 latency reversal using a luciferase reporter assay in TZM-bl cells. The 50% ethanolic extract of G. kraussiana showed the highest LTR activation (EC50 = 3.75 μg/mL) with no significant cytotoxicity observed. Bioactivity-guided fractionation of the Gnidia kraussiana extract led to the isolation of gnidilatidin, a daphnane-type diterpenoid, using ultrahigh-performance liquid chromatography coupled with high-resolution mass spectrometry (UHPLC-HRMS). Gnidilatidin demonstrated potent latency-reversing activity (EC50 = 5.49 nM in J-Lat 10.6 cells) and downregulated CD4 and CXCR4, suggesting enhanced inhibition of HIV-1 entry. This study supports the ethnopharmacological relevance of G. kraussiana and validates its traditional use. It also identifies gnidilatidin as a promising lead compound for HIV-1 latency-reversal-based strategies. Further studies are needed to optimize its pharmacological profile and further elucidate its therapeutic potential, particularly as part of an optimized combination regimen with combination antiretroviral therapy (cART).